(untitled) (Agricultural Engineering, 2017)
The article includes analysis of expert system application possibilities in the environment of production processes control. Such concepts as artificial intelligence, expert system, intellectual factor, state space were used. The object of the research consisted of the mechanism of controlling an enterprise (manager). These mechanisms were analysed from the point of view of state space. The graph method was used to visualize information presentation. Analysis of control processes of an enterprise was carried out by determination of their state space. The concept of state space itself is completed with numerous measurement values (parameters) under influence of which the process of task solution takes place. Moreover, the concept of static and dynamic elements of state space of the control system is applied. It was shown that dynamic elements enable the quality presentation of space, which without including other restrictions leads to extension of its impact, which confirms that a given system has an intelligent factor.